The "Elevatio Animae" in the Medieval Funerary Art of the Iberian Peninsula - Ramos Dias, Marta Miriam (Eikón / Imago, 2014)
The elevatio animae symbolizes the instant in which the soul migrates to Paradise. The most common representation of this moment depicts the soul as a naked child, encased in a cloth, which is being pulled by two angels in an upward direction. The first (known) examples of this iconography were depicted in architectonical elements, namely, capitals. Later, the elevatio animae appeared, mainly, in tombs of the 13th and 14th centuries. In this study, we will analyze some typologies with depictions of the elevatio animae integrated in different iconographic contexts.
Keywords: Soul; Ascension; Angels; Tombs; Iconography